Longitudinal and Comparative Measures of Serum Chitotriosidase and YKL-40 in Patients With Idiopathic Pulmonary Fibrosis - Majewski, Sebastian; Szewczyk, Karolina; Jerczyńska, Hanna; Miłkowska-Dymanowska, Joanna; Białas, Adam J.; Gwadera, Łukasz; Piotrowski, Wojciech J. (Frontiers in Immunology, 2022)
Background: Although chitin is absent in humans, chitinases are present in healthy subjects and show dysregulated expression in a variety of diseases resulting from abnormal tissue injury and repair responses. It was shown that chitotriosidase (chitinase 1/CHIT1) and structurally-related chitinase 3-like 1 protein (CHI3L1/YKL-40) play important roles in the pathobiology of idiopathic pulmonary fibrosis (IPF), however little is known about their longitudinal serum levels and relationship to clinical measures in IPF. Methods: The present study is the first to evaluate serial measurements of serum CHIT1 activity and YKL-40 concentrations in patients with IPF starting antifibrotic treatment and followed up for 24 months. In addition, baseline serum CHIT1 and YKL-40 were compared between patients with IPF and control subjects, and possible CHIT1 and YKL-40 relationships to longitudinal clinical assessments in IPF were explored. Results: Baseline serum CHIT1 activity and YKL-40 concentrations were significantly elevated in patients with IPF compared to control subjects and showed similar discriminatory ability in distinguishing IPF from controls. No significant differences between the median serum CHIT1 activity and YKL-40 concentration measured over a study follow-up were noted. We found significantly elevated baseline serum CHIT1 activity in the progressors compared with the stables in the first year, while significantly increased baseline serum CHIT1 activity was noted in the stables compared to the progressors in the second year. Additionally, we observed a significant negative correlation between a change in serum YKL-40 concentration and a change in forced vital capacity (FVC) % predicted (% pred.) in the stables subgroup, whereas, a change in serum CHIT1 activity correlated negatively with a change in FVC% pred. in the progressors subgroup. Conclusions: This explorative study findings add further evidence that CHIT1 and YKL-40 are upregulated in patients with IPF, and suggest that longitudinally stable serum CHIT1 activity and YKL-40 concentration levels may potentially be associated with the antifibrotic treatment response. In addition, our findings are supporting the possible role of CHIT1 and YKL-40 as candidate diagnostic and prognostic biomarkers in IPF. Further research is needed to validate present study findings.